REGIONAL DIFFERENCES BETWEEN JOB SEEKERS: CASE OF LATVIA - Lase, Kate; Sloka, Biruta (University of Latvia, 2021)
Differences in labour market have always been on great importance in Latvia, however special concern is about regions of Latvia where finding a new job sometimes could be very challenging process, because these regions are developing unevenly, job vacancies are limited, wages are lower and there is a lack of high qualified specialists in labour market. Purpose of the study is to analyse regional differences between job seekers in regions in Latvia. The tasks of the study: 1) To analyse theoretical background of regional differences of job seekers and employment in context of urban and rural areas; 2) To analyse main challenges and problems of regional differences between job seekers in regions in Latvia. Research methods used in preparation of the paper were the analysis of scientific publications and previous conducted research results, the analysis of Labour Force Survey results and the analysis of data of Central Statistical Bureau of Latvia. The Survey results are analysed using indicators of descriptive statistics (indicators of central tendency or location - arithmetic mean, mode, median), indicators of variability (indicators of dispersion - range, standard deviation and standard error of mean), cross-tabulation for regions of Latvia, for territories: urban-rural living and analysis of variance - ANOVA are used. The results of analysis have indicated several differences between regions of Latvia, but there are no differences between job seekers in urban and rural areas of Latvia.
Keywords: employment; job search; regional differences; Research Subject Categories::SOCIAL SCIENCES::Business and economics